Multiplex immune protein profiling of fine‐needle aspirates from patients with non‐small‐cell lung cancer reveals signatures associated with PD‐L1 expression and tumor stage. Issue 11 (1st May 2021) - Franzén, Bo; Viktorsson, Kristina; Kamali, Caroline; Darai‐Ramqvist, Eva; Grozman, Vitali; Arapi, Vasiliki; Hååg, Petra; Kaminskyy, Vitaliy O.; Hydbring, Per; Kanter, Lena; Nyrén, Sven; Ekman, Simon; et al.
Abstract : Biomarker signatures identified through minimally invasive procedures already at diagnosis of non‐small‐cell lung cancer (NSCLC) could help to guide treatment with immune checkpoint inhibitors (ICI). Here, we performed multiplex profiling of immune‐related proteins in fine‐needle aspirate (FNA) samples of thoracic lesions from patients with NSCLC to assess PD‐L1 expression and identify related protein signatures. Transthoracic FNA samples from 14 patients were subjected to multiplex antibody‐based profiling by proximity extension assay (PEA). PEA profiling employed protein panels relevant to immune and tumor signaling and was followed by Qlucore ® Omics Explorer analysis. All lesions analyzed were NSCLC adenocarcinomas, and PEA profiles could be used to monitor 163 proteins in all but one sample. Multiple key immune signaling components (including CD73, granzyme A, and chemokines CCL3 and CCL23) were identified and expression of several of these proteins (e.g., CCL3 and CCL23) correlated to PD‐L1 expression. We also found EphA2, a marker previously linked to inferior NSCLC prognosis, to correlate to PD‐L1 expression. Our identified protein signatures related to stage included, among others, CXCL10 and IL12RB1. We conclude that transthoracic FNA allows for extensive immune and tumor protein profiling with assessment of putative biomarkers of important for ICI treatment selection in NSCLC. Abstract : We analyzed fine‐needle aspirate (FNA) samples of thoracic lesions of non‐small‐cell lung cancer (NSCLC) patients by multiplex protein profiling. Data analysis revealed immune and oncogenic signaling proteins correlated to PD‐L1 expression and tumor stage. Results show that minimally invasive FNA sampling permits profiling of key proteins which may open for longitudinal monitoring to guide immune therapy in NSCLC.